Nanomaterial-Based Drug Delivery Carriers for Cancer Therapy - Feng, Tao.; Zhao, Yanli; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This brief summarizes different types of organic and inorganic nanomaterials for drug delivery in cancer therapy. It highlights that precisely designed nanomaterials will be the next-generation therapeutic agents for cancer treatment.
Current status of cancer and the characteristics of cancer -- Clinical anticancer drug for cancer treatment -- Nanomaterials-based drug carriers for cancer therapy -- Conclusions.
Keywords: Biomedical engineering; Cancer; Biomaterials; Microtechnology; Microelectromechanical systems; Medicine -- Research; Biology -- Research; Clinical biochemistry; Biomedical Engineering and Bioengineering; Cancer Biology; Biomaterials; Microsystems and MEMS; Biomedical Research; Medical Biochemistry